1998
DOI: 10.1007/s002130050506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the potassium channel blockers, apamin and 4-aminopyridine, on scopolamine-induced deficits in the delayed matching to position task in rats: a comparison with the cholinesterase inhibitor E2020

Abstract: The effects of the muscarinic antagonists, scopolamine HBr and MeBr, a cholinesterase inhibitor, E2020, and K+ channel blockers, 4-aminopyridine (4-AP) and apamin, on the performance of rats in a delayed matching to position (DMTP) task were examined. The percentage of correct choices (choice accuracy), number of trials completed and intertrial intervals were measured. Discriminability and response bias were also calculated, using signal detection analysis. Scopolamine HBr (0.1 mg/kg), but not scopolamine MeBr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Moreover, these findings are consistent with observations that donepezil improves attention or acquisition processes in patients with Alzheimer's disease (Sahakian and Coull, 1993) and reports that the cholinergic system is involved in attentional processes (Voytko et al, 1994;Muir, 1997;Muir et al, 1999). Several studies have reported that donepezil has no effect or impairs performance in healthy rodents, but that it reverses deficits induced pharmacologically or by brain lesions (Rupniak et al, 1997;Poorheidari et al, 1998;Higgins et al, 2002;Bontempi et al, 2003;Takahashi et al, 2005;Yamada et al, 2005). Donepezil also improves performance of aged rats and mice in the Morris water maze (Hernandez et al, 2006), as well as in spontaneous alternation in the T-maze and in a delayed nonmatch to place task in the radial-arm maze (Bontempi et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, these findings are consistent with observations that donepezil improves attention or acquisition processes in patients with Alzheimer's disease (Sahakian and Coull, 1993) and reports that the cholinergic system is involved in attentional processes (Voytko et al, 1994;Muir, 1997;Muir et al, 1999). Several studies have reported that donepezil has no effect or impairs performance in healthy rodents, but that it reverses deficits induced pharmacologically or by brain lesions (Rupniak et al, 1997;Poorheidari et al, 1998;Higgins et al, 2002;Bontempi et al, 2003;Takahashi et al, 2005;Yamada et al, 2005). Donepezil also improves performance of aged rats and mice in the Morris water maze (Hernandez et al, 2006), as well as in spontaneous alternation in the T-maze and in a delayed nonmatch to place task in the radial-arm maze (Bontempi et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…In fact, AChE inhibitors, such as tacrine and E2020, are thought to augment cholinergic neurotransmission by preventing the hydrolysis of extracellular ACh (20,21). These compounds have been reported to improve the cognitive dysfunction in patients with Alzheimer's disease (22 -24) and in animal models of amnesia (20,25,26). On the other hand, tremor, hypothermia, hypersalivation, chewing and yawning induced by muscarinic agonists are well-recognized central or peripheral cholinomimetic side effects (27 -29).…”
Section: Discussionmentioning
confidence: 99%
“…The same improving effect of donepezil on scopolamine-induced deficit in the radial maze task was reported by other researchers (51,52), who used donepezil as a reference drug to evaluate their compounds. In other scopolamine-induced models, donepezil partially, but significantly counteracted scopolamine-induced delayedmatching-to-position task in rats (53,54). Rupniak et al (55) showed that donepezil inhibited scopolamine-induced deficit in spatial and visual recognition memory tasks in rhesus monkeys.…”
Section: Behavioral Pharmacologymentioning
confidence: 99%